Mamíferos del pleistoceno superior de santiago del estero (Argentina) y sus afinidades paleobiogeográficas - Chimento, Nicolás R.; Agnolin, Federico L. (Papéis Avulsos de Zoologia, 2011)
A new mammalian assemblage from the Upper Pleistocene of the Dique "Los Quiroga" locality (Santiago del Estero province, Argentina), positioned in the Chaco Region is here described. The material here described were collected from fine sand and shale deposits of an unnominated stratigraphic unit. Panochthus greslebini and Mixotoxodon larensis, are described for the first time for the country, and Holmesina paulacoutoi and Toxodon gracilis are reported for the first time for such geographic region. An analysis of the present material, together with previous studies in the zone suggest more favourable climatic conditions than proposed by previous authors, as well as stronger biogeographic ties together with the Mesopotamia Region.